TRACING THE EVOLUTION OF LIGHTING IN ARCHITECTURE - Ferry Gunawan; Yandi Andri Yatmo; Paramita Atmodiwirjo (Journal of Architecture&ENVIRONMENT, 2022)
The role of light has been studied, examined, and analyzed for the built environment from ancient times. The methodology was conducted by literature review and precedents study to determine shifts in viewpoints that become the basis of architectural lighting design practice. This paper will discuss four evolution viewpoints but understanding the sky with its properties is the first step before moving forward. The first evolution will focus on light's role from perception to narration; the second one will examine light from the point of development of aperture to performance; the third will investigate light from material to immaterial with a particular focus on light's immateriality from the point of view of J.J. Gibson, and the last part will have an overview of light's purpose from quantitative value to its contemplative tranquillity. All four evolutions will provide broad strokes from one extreme to the other to highlight the shift of lighting knowledge and applications.